A Proposed Ratchaburi’s Tourism Strategic Execution Model to Strengthen Cultural Tourism Development: A Case of Ratchaburi Province, Thailand - Itthiophakorn, Dhouchatorn; Preudhikulpradab, Sirichai (Journal of Thai Hospitality and Tourism, 2025)
This mixed-methods research has three objectives, which are 1) to examine the current situations of factors that influence destination loyalty from the perspective of Ratchaburi's cultural tourism development and deployment, 2) to explore the common perspectives of key informants on the strategic execution of Ratchaburi's cultural tourism development and deployment, and 3) to propose the strategic execution model for cultural tourism to strengthen the overall tourism potential and attractiveness. The target population is Thai people who have domestic traveling experience to the central province of Ratchaburi. The researcher utilized structured questionnaires for quantitative sections and in-depth interviews for qualitative sections. Key findings illustrate that the factors influencing destination loyalty that are most significant are authentic experiences, meaningfulness, local culture, destination image, and a memorable tourism experience, followed by involvement and lastly knowledge. Derived themes from the qualitative section are also ranked based on their repeating frequency. Both results were juxtaposed to form a proposed strategic execution model. Additionally, the proposed model is validated by three experts through the Delphi technique utilization for two rounds. Recommendations for strengthening destination loyalty towards cultural tourism development are accessibility of cultural knowledge, capability-building initiatives, creative tourism activities, innovative and smart promotion, and coordinative local engagement.